PENGEMBANGAN BIOTEKNOLOGI PUPUK HIJAU PLUS BERBASIS VEGETASI SEKUNDER UNTUK MENINGKATKAN PRODUKSI KACANG TANAH LOKAL PADA LAHAN KERING MARGINAL - RAHNI, NINI MILA; -, LA KARIMUNA (Jurnal Agroteknos, 2014)
The objective of this study was to increase growth and yield of three local peanut genotypes by application of green manure. The pot experiment was carried out at Watuputih, Muna, Southeast Sulawesi. Completely Randomized Design was used in a factorial pattern, replicated three times.  The first factor was genotype of local peanut, consisted of 3 genotypes, namely : (1) Wadaga, (2) Lasehao and (3) Parigi, and the second factor was green manure, consisted of 4 application rates, namely : (1) 0 ton ha-1, (2) 5 ton ha-1, (3) 10 ton ha-1 and (4) 15 ton ha-1.The experiment results showed that application of green manure had significant effects on increased N and P nutrient uptake, nitrat reductase enzymes, yield components and yields.  Parigi genotype response to application of green manure was better than Wadaga and Lasehao. Key words : Genotype, Peanut, Ultisols, Green manure.